Coronavirus pandemic reduced China’s CO(2) emissions in short-term, while stimulus packages may lead to emissions growth in medium- and long-term - Wang, Qingqing (Appl Energy, 2020)
Coronavirus has confined human activities, which caused significant reductions in coal, oil, and natural gas consumptions in China since January of 2020. We compile industrial, transport, and construction data to estimate the reductions in energy-related CO(2) emissions during the first quarter of 2020 in China. Our results show that the fossil fuel related CO(2) emissions decreased by 18.7% (182 MtCO(2)) in the first quarter of 2020 compared with the same period last year, including reductions of 12.2% (92 MtCO(2)) in industry sectors, 61.9% (62 MtCO(2)) in transport, and 23.9% (28 MtCO(2)) in construction. The figure in annual CO(2) emission reductions is expected to limit with an estimate of 1.6%. However, to achieve the economic target for the 13th Five-Year-Plan, stimulus packages including investments in “shovel-ready” infrastructure projects issued by China’s central and local governments to response the COVID-19 may increase CO(2) emissions with a higher speed in the coming years. Thus, sustainable stimulus packages are needed for accelerating China’s climate goals.